Computer modeling for pharmacological treatments for dystonia. (2016) - Neymotin, Samuel A.; Dura-Bernal, Salvador; Moreno, Herman; Lytton, William W.
Abstract : Dystonia is a movement disorder that produces involuntary muscle contractions. Current pharmacological treatments are of limited efficacy. Dystonia, like epilepsy is a disorder involving excessive activity of motor areas including motor cortex and several causal gene mutations have been identified. In order to evaluate potential novel agents for multitarget therapy for dystonia, we have developed a computer model of cortex that includes some of the complex array of molecular interactions that, along with membrane ion channels, control cell excitability.